THE INFLUENCE OF WORK DISCIPLINE, MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE PT. SDF - Slamet, Sofiyah Rokhmawati; Heru Baskoro (Ikatan Dosen Menulis, 2025)
This research was carried out at PT SDF. The aim of this research is to determine the influence of discipline (X1), motivation (X2) and job satisfaction (X3), which influence employee performance (Y) at PT. SDF partially. The population in this research is all employees at PT SDF, totaling 49 employees. The sampling technique method uses a saturated census technique with a sample size of 49 respondents. The data analysis technique in this research is multiple linear regression using SPSS 25. The results of this research show that the Discipline variable (X1) has no effect on Employee Performance. Motivation (X2) and Job Satisfaction (X3) partially influence employee performance. The coefficient of determination (R2) of 0.639 shows that the influence of the three independent variables together on the dependent variable is 63.9%